The association of alcohol use and positive and negative urgency to same day objective binge eating in emerging adults - Fischer, Sarah; Wonderlich, Joseph; Miller, Leo A.; Breithaupt, Lauren; Frietchen, Rachel; Cao, Li; Nelson, Jillian D.; Izquierdo, Alyssa (Frontiers in Psychology, 2023)
Objective binge eating and problematic alcohol use often co-occur and are common behaviors in emerging adults. Both behaviors are thought to be driven by affect regulation processes. Objective binge eating often occurs in the context of increasing or acute negative affect, and often occurs in solitude. Alcohol use in emerging adults can also be associated with negative affect regulation. However, in contrast to objective binge eating, a large body of research indicates that there are positively valenced pathways to alcohol use in this age group. Emerging adults often drink socially, to enhance enjoyment, and in the context of positive mood. We propose that one pathway to objective binge eating in this developmental period is through alcohol use itself, such that emerging adults who consume alcohol and who are more likely to act impulsively in the context of positive emotion (have high levels of positive urgency) may be more likely to binge eat following drinking. We collected data using ecological momentary assessment in 106 undergraduates on positive and negative affect, motives for drinking and eating, and alcohol use and objective binge eating, in addition to baseline questionnaires of impulsivity. There were no significant changes in affect prior to drinking in this sample. Alcohol use at one time point significantly increased odds of objective binge eating at a later time point in the same day. Individual differences in positive urgency, the tendency to act rashly while experiencing positive affect, were also associated with increased odds of objective binge eating that occurred after alcohol use. Individual differences in negative urgency, the tendency to act rashly after experiencing negative affect, did not have a main effect on objective binge episodes, but did interact with alcohol use to increase the odds of objective binge eating following drinking. The vast majority of drinking episodes prior to objective binge eating were social drinking episodes, and participants most commonly endorsed “to have fun” as a reason for drinking. Results suggest that alcohol consumption may increase risk for objective binge eating in emerging adults.